Evaluating a DVD promoting breast awareness amongst Black women aged 25-50 in East London - Greenhough, B; Dembinsky, M; Dyck, I; Brown, T; Robson, J; Homer, K; Sajani, C; Carter, L; Duffy, S; Ornstein, M (BMJ Publishing Group, 2016)
Background The mean age of presentation for breast cancer amongst Black women is substantially earlier than their White counterparts. Black women also present with adverse prognostic factors that have major clinical implications, including lower survival. To pilot the use of a six-minute DVD on breast cancer in young (under 50) Black women to raise awareness and examine the impact of the DVD on increased consultation and referral rates amongst these women. Methods Two general practices (intervention practices) in the Hackney area were randomised to have the DVD mailed to all Black women aged 25-50 registered with the practices, and two practices to no intervention (control practices). EMIS data was used to compare consultation rates pre and post intervention, in both the intervention and control practices. Interviews with practice staff and focus groups with patients in participating practices provided qualitative data on the study context and DVD effectiveness. Results A trend of declining consultations for breast symptoms was observed (-22% and -31% amongst non-Black women in the control and intervention practices and -23% amongst Black women in the control practice) except among the target population of Black women aged 25-50 for the DVD in the intervention practices, which saw an increase of 28% in consultations. The qualitative data indicated that the DVD was well received in the target population, and suggested further ways of disseminating awareness messages and overcoming barriers to help-seeking. Conclusion Pilot results suggest that the strategy of distributing the DVD may increase consultations for breast problems.